FEMINISM STUDY: FASHION DETERMINING WOMAN POWER IN THE MOVIE ENTITLED â€œTHE DEVIL WEARS PRADAâ€ - Shylvia Lisdiana Ayu Febriyanto; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2024)
This research aims to describe fashion and feminism in the film The Devil Wears Prada. This research aims to understand the picture of fashion in the world of work and explain the lifestyle changes experienced by the female character, Andy.Â This research analyzes fashion can express self-confidence and even social class.Â In this research, the researcher uses Ebunoluwa's theory about feminism.Â The research method used is descriptive qualitative.Â The research method also uses two approaches, the feminist and sociological approaches.Â The results of the analysis show that fashion is depicted as an important thing in the film The Devil Wears Prada and the impact of Andy's change into a fashionable woman. Fashion in this film can show a person's values and social class.Â Andy's new appearance is also balanced by her ability to fulfill all of Miranda's job demands, which she can do perfectly. So not only has her appearance changed, but Andy is also more competent in her job.